Effect of low to moderate levels of smoking and alcohol consumption on serum immunoglobulin concentrations. - McMillan, S A (1997)
AIM: To determine the effect of low to moderate levels of smoking and alcohol consumption on immunoglobulin concentrations. METHODS: Serum samples from 1787 subjects with approximately equal numbers in each five year group from 15 to 64 years were obtained from a large random population survey in Northern Ireland. Details were available on each subject concerning the number of units of alcohol consumed per week and the number of cigarettes smoked per day. IgG, IgM, and IgA concentrations were measured by laser nephelometry on all serum samples. RESULTS: Low to moderate consumption of alcohol was associated with a decrease in IgG and IgM median concentrations in contrast to an increase in IgA median concentrations. The decrease in IgM and especially IgG median concentrations appeared to be related to the smoking habits of the subjects. Alcohol consumption alone was associated with increased IgA median concentrations whereas cigarette smoking alone was associated with reduced IgG median concentrations. CONCLUSION: Low levels of alcohol consumption and cigarette smoking influence IgG, IgM, and IgA serum concentrations. This should be borne in mind when selecting subjects for use in research and clinical settings.